Surgical Treatment of Anomalous Origin of Right Coronary Artery in a Patient with Mitral Stenosis - Refatllari, Ali (Open Access Maced J Med Sci, 2016)
BACKGROUND: An anomalous origin of the right coronary artery is rarely observed, with a reported incidence between 0.026% and 0.25%. This condition is often completely asymptomatic and is found incidentally during angiographic evaluation for other cardiac diseases. However some patients present with exertion angina or sudden death. Surgical treatment in patients with anomalous RCA is still controversial. Treatment can be conservative, angioplasty or surgery. CASE PRESENTATION: A 59-year-old man was admitted with severe mitral stenosis. He complained exertion and rest dyspnea, NYHA III class. He had sequels of embolic stroke, results of left atrial thrombus. Echocardiography showed calcified severe mitral stenosis with mitral orifice area of 1.1 square centimeters with PSPAP 60 mmHg and normal LV function. Routine coronary angiography before surgery showed aberrant origin of RCA from the left sinus of Valsalva with 90% stenosis at his origin. Multi-slice computed tomography proved the diagnosis of anomalous RCA arising from the left sinus of Valsalva and taking an inter-arterial course between the aorta and pulmonary artery. The patient underwent mitral valve replacement with mechanical St. Jude prosthesis No 29 and saphenous vein graft to RCA. We chose by-pass grafting techniques because after aortotomy, RCA was too close to LMCA, intramural course was too short and stenosis of RCA was outside of aortic wall. The patient’s perioperative course was without complications and patient was discharged on the seventh postoperative day. CONCLUSION: Correction of anomalous of the origin of right coronary artery is mandatory in cases where patient has to be operated for other cardiac causes.